REGARDING THE FUNCTIONS OF SMALL ENTERPRISES DURING THE MARTIAL STATE - КUKLINOVA Tетіана (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The paper presents the results of study of the functioning of small enterprises in the context the martial state. The study shows the importance of small enterprises in Ukraine. The work deals with the key aspects of small enterprises functioning during the martial state. The specificity of small enterprises in the context the martial state analyzed in Ukraine. The article shows the activities of small enterprises during wartime. Considered aspects of their functioning during military aggression in conditions of uncertainty. The specifics and peculiarities of their relocation have been revealed in the work. The specifics and features of their problems have been revealed on the basis of a detailed analysis of the process of their functioning. Their functioning was studied with regard to logistic processes in a paper. Main problems of small enterprises are defined in a study. The necessity of stimulating small enterprises in Ukraine is indicated. The results also showed the importance of logistic processes during wartime for enterprises in Ukraine. The main features of small enterprises in Ukraine have been revealed during the martial state. The paper deals with problems of the stimulation of small enterprises in the context the martial’s state. Recommendations for their support and restoration in the post-war period have been formulated in a paper. The purpose of the article is to characterize the current state and trends in the functioning of small enterprises during wartime and to develop recommendations for their support and restoration. The article substantiates the need to find tools for their support and restoration, both during a full-scale invasion and in the post-war period. Problems of foreign economic activity of small enterprises has been shown in the presented work.